Differential Processing of Consonance and Dissonance within the Human Superior Temporal Gyrus - Foo, Francine; King-Stephens, David; Weber, Peter; Laxer, Kenneth; Parvizi, Josef; Knight, Robert T. (Frontiers in Human Neuroscience, 2016)
The auditory cortex is well known to be critical for music perception, including the perception of consonance and dissonance. Studies on the neural correlates of consonance and dissonance perception have largely employed non-invasive electrophysiological and functional imaging techniques in humans as well as neurophysiological recordings in animals, but the fine-grained spatiotemporal dynamics within the human auditory cortex remain unknown. We recorded electrocorticographic (ECoG) signals directly from the lateral surface of either the left or right temporal lobe of 8 patients undergoing neurosurgical treatment as they passively listened to highly consonant and highly dissonant musical chords. We assessed ECoG activity in the high gamma (γhigh, 70-150 Hz) frequency range within the superior temporal gyrus (STG) and observed two types of cortical sites of interest in both hemispheres: one type showed no significant difference in γhigh activity between consonant and dissonant chords, and another type showed increased γhigh responses to dissonant chords between 75-200ms post-stimulus onset. Furthermore, a subset of these sites exhibited additional sensitivity towards different types of dissonant chords. We also observed a distinct spatial organization of cortical sites in the right STG, with dissonant-sensitive sites located anterior to non-sensitive sites. In sum, these findings demonstrate differential processing of consonance and dissonance in bilateral STG with the right hemisphere exhibiting robust and spatially organized sensitivity towards dissonance.